Dampak Tempat Penyimpanan Jamur Sebagai Koleksi Biakan Murni di Laboratorium Untuk Ketersediaan Bahan Praktikum - Armi Junita; Neny Afridayanti; Nurhayani Nurhayani (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Junita A, Afridayanti N, Nurhayani N. 2021. The impact of microbible fungi storage as pure culture collections in the laboratory to keep availability of practical materials. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 826-834. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Microbial fungi are one of the main ingredients used for both practicum and research in the laboratory. The methods used in this study were experimental methods, documentation and data analysis. The treatments used were three isolates of microbial fungi, namely Aspergillus sp, Trichoderma sp and Penicillium sp as a comparison, and each replicate per isolate was carried out in five replicates which were then stored in a storage device, the observation time was carried out for five months with an interval of one month of observation. The purpose of this study was to determine the effect of storage on the growth of microbial fungi Aspgillus sp, Trichoderma sp and Penicillium sp stored in Incubators, Ice cabinet, and Germinators both in the short and long term. The results showed that the best place for fungi based on morphological texture, color, thickness of mycelium, diameter of hyphal growth and physiological fungi was stored in an incubator, we can see this based on research data where the percentage of hyphal growth is the fastest stored in the incubator, and the growth of hyphae is the fastest. the slowest being stored in the ice cabinet, not only hyphae growth, the fungal media in the incubator is more humid, the mycelium is thicker, and the color of the spores/conidia is lighter, the physiological shape of the conidia is also larger, because the nature of the media is more humid so the shelf life of mushrooms can also be higher. long. Meanwhile, the fungus stored in the germinator had good hyphal growth, but the media was easier to contaminate, the temperature